Effect of Polypropylene Fiber Dimensions on Undrained Compressive Strength of Silt Soil - Yılmazoğlu, Mehmet Uğur (ACADEMY Saglik Hiz. Muh. Ins. Taah. Elekt. Yay. Tic. Ltd. Sti., 2024)
In the study where the effect of polypropylene (PP) fibers on the mechanical properties of low plasticity silt soils was investigated, unconfined compressive strength (UCS) tests were carried out by adding PP fiber additives to the soil at different rates (0%, 0.4%, 0.8%, 1.25%) and lengths (6 mm and 12 mm). The Taguchi method analyzed the experimental results using signal-to-noise (SN) ratios. The findings show that PP fiber additive significantly increases the strength and ductility behavior of the soil. It was determined that the unconfined compressive strength also increased with the increase in the fiber ratio. It was also determined that the fiber size was adequate on the strength. While 6 mm long fibers provided a more regular and stable strength increase, it was determined that the effect of 12 mm long fibers varied depending on the fiber ratio in the mixture. A significant 1.25% fiber ratio and 6 mm long fibers were determined to give optimum results. SN analysis results were evaluated according to the "bigger is better" principle, and the highest SN ratios were obtained at 1.25% fiber ratio. The study results show that PP fibers are an effective additive in improving low-plasticity silty soils and provide an economical solution. These results show the usability of PP fibers in soil engineering projects.